Tracking conical intersection passage with time-resolved resonant Auger scattering - Wang, Chao; Kimberg, Victor; Gong, Maomao; Cheng, Yongjun; Liu, Xiao-Jing; Vendrell, Oriol; Ueda, Kiyoshi; Zhang, Song Bin (Physical review, 2024)
Through nonadiabatic vibrational dynamics, conical intersection (CI) couples electronic states and opens ultrafast nonradiative reaction channels. To reveal and track the unique pathways of CI using ultrashort x-ray pulses, several time-resolved x-ray spectroscopies (such as photoelectron, absorption, and Raman) have been proposed. In this work, we investigate time-resolved resonant Auger scattering, utilizing femtosecond to attosecond x-ray probe pulses, to detect ultrafast nonadiabatic electron-nuclear dynamics through the CI triggered by an ultrashort UV pump pulse. Our simulations indicate that the electronic coherence signal from the wave packet passing through the CI pathways is influenced by the core-excited potential and its lifetime broadening due to the dynamical contribution from bound nuclear degrees of freedom. Given the prevalence of CIs in polyatomic molecules and their wide range of applications, this study offers a new perspective on monitoring nonadiabatic dynamics in photochemistry and photophysics using ultrashort x-ray pulses.
Gesehen am 30.04.2025